A phenomenological investigation into the psychotherapist's experience of identifying, containing and processing the patient's projective identifications - Thorpe, Mark Richard (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The aim of the study was to describe the therapist's lived experience of identifying, containing and processing the feelings, thoughts or fantasies evoked in him by the patient's projective identifications. A question which would elicit the experience of this phenomenon was formulated by examining case histories, and modified through the use of individual pilot studies. Fifteen experienced, psychoanalytically oriented psychotherapists were interviewed. The eight psychologically richest accounts were chosen for the study. Using the empirical phenomenological method, the four protocols that most clearly reflected the phenomenon were analysed in detail, while the remaining four were used to clarify areas of uncertainty. Projective identification is conceptualised as the process whereby the patient coerces the therapist to embody an un-appropriated aspect of his (patient's) world. The context of processing a patient's projective identification was discovered to be such that the therapist finds himself coerced to embody an incongruent, unfamiliar, confusing and inauthentic state of being which is consonant with the patient's perception of him. The discomfort of the experience leads the therapist to bring to awareness and thematise his feeling-state. He alternates between avoiding this state of being, which results in conf1ict with the patient and the therapist's own values, and appropriating it, which feels inauthentic. The therapist moves from a position of trying to understand the experience in relation to his own world, to the realisation that it is co-determined by the patient. From a position of reflective distance he re-appropriates aspects of his world that were closed to him while under the influence of the patient, in addition to appropriating previously unowned aspects. The therapist dialogues these appropriations with the invoked feelings, allowing him to differentiate those aspects of his feeling-state which are authentically his from those which are unowned aspects of the patient's aspects of his world that were closed to him while under the influence of the patient, in addition to appropriating previously unowned aspects. The therapist dialogues these appropriations with the invoked feelings, allowing him to differentiate those aspects of his feeling-state which are authentically his from those which are unowned aspects of the patient's world that he has been forced to embody. Through this process the therapist clarifies and gives meaning to his feelings. The therapist fee1s re1ieved and lighter, when in the service of the therapy, he temporarily gives himself over to the patient's experience of him, without feeling drawn to either disowning or appropriating it, while simultaneously remaining open to his own authentic reality. These findings were dialogued with the literature on projective identification.
Keywords: Psychotherapist and patient; Psychotherapy -- Methods